Dampak Pembangunan Jalan Tol Trans Pekanbaru-Bangkinang terhadap Penjual Makanan Tradisional Lopek Bugi Danau Bingkuang - Ruli Hamsana; Resdati Resdati (Laboratory of Anthropology Department, Faculty of Humanity, Halu Oleo University, 2025)
The construction of toll roads is a national government development project aimed at connecting various regions with faster and easier transportation routes. The construction of toll roads brings various impacts on the surrounding environment, both positive and negative, especially in the areas they pass through. Toll road development is one of the essential infrastructures designed to improve connectivity and transportation efficiency between regions. However, the impact of toll road construction on traders, both small and large, often becomes a significant concern. This study aims to analyze the impact of toll road construction on